PERKEMBANGAN KURIKULUM MADRASAH DI INDONESIA - Asrofi, Asrofi; Adibah, Ida Zahara (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT Madrasahs have existed since before independence and were officially recognized as part of the national education system after Indonesia gained independence. The madrasah curriculum was then adjusted to align with general education without losing its Islamic identity. This article discusses the dynamics and long journey of madrasah curriculum development in Indonesia from the colonial era to the post-independence period. Through a literature study method, this article explores educational policies governing madrasahs as part of the national education system, including the integration of religious and general curricula, by collecting and analyzing relevant written sources from various academic databases using specific keywords. The collected data are then descriptively analyzed to provide an overview. Madrasahs have transformed from religious-based self-help institutions into formal educational institutions legally recognized by the state. Amid challenges such as limited resources and the quality of teaching staff, madrasahs continue to make a significant contribution to the nation's intellectual development. This article emphasizes the importance of developing a madrasah curriculum based on Islamic values that can also respond to global challenges through a holistic and contextual approach. With a strong philosophical, psychological, sociological, and organizational foundation, the madrasah curriculum is expected to meet the needs of an inclusive and quality national education. ABSTRAK Madrasah telah ada sejak sebelum kemerdekaan dan mulai diakui secara resmi sebagai bagian dari sistem pendidikan nasional setelah Indonesia merdeka. Kurikulum madrasah pun disesuaikan agar selaras dengan pendidikan umum tanpa menghilangkan identitas keislamannya. Artikel ini membahas dinamika dan perjalanan panjang perkembangan kurikulum madrasah di Indonesia sejak masa kolonial hingga era pasca kemerdekaan. Melalui Melalui metode studi literatur, artikel ini menelusuri kebijakan-kebijakan pendidikan yang mengatur madrasah sebagai bagian dari sistem pendidikan nasional, termasuk integrasi kurikulum agama dan umum, dengan mengumpulkan dan menganalisis sumber-sumber tertulis yang relevan dari berbagai database akademik menggunakan kata kunci tertentu. Data yang diperoleh kemudian dianalisis secara deskriptif untuk memberikan gambaran. Madrasah mengalami transformasi dari lembaga swadaya berbasis keagamaan menjadi institusi pendidikan formal yang diakui secara yuridis oleh negara. Di tengah tantangan seperti keterbatasan sumber daya dan kualitas tenaga pengajar, madrasah tetap memiliki kontribusi signifikan dalam mencerdaskan kehidupan bangsa. Artikel ini menekankan pentingnya pengembangan kurikulum madrasah yang berlandaskan pada nilai-nilai Islam serta mampu merespons tantangan global melalui pendekatan yang holistik dan kontekstual. Dengan landasan filosofis, psikologis, sosiologis, dan organisatoris yang kuat, kurikulum madrasah diharapkan mampu menjawab kebutuhan pendidikan nasional yang inklusif dan berkualitas.